Functional Analysis of the N-Acetylglucosamine Metabolic Genes of Streptomyces coelicolor and Role in Control of Development and Antibiotic Production - Świątek, Magdalena A. (American Society for Microbiology, 2012)
N-Acetylglucosamine, the monomer of chitin, is a favored carbon and nitrogen source for streptomycetes. Its intracellular catabolism requires the combined actions of the N-acetylglucosamine-6-phosphate (GlcNAc-6P) deacetylase NagA and the glucosamine-6-phosphate (GlcN-6P) deaminase/isomerase NagB. GlcNAc acts as a signaling molecule in the DasR-mediated nutrient sensing system, activating development and antibiotic production under poor growth conditions (famine) and blocking these processes under rich conditions (feast). In order to understand how a single nutrient can deliver opposite information according to the nutritional context, we carried out a mutational analysis of the nag metabolic genes nagA, nagB, and nagK. Here we show that the nag genes are part of the DasR regulon in Streptomyces coelicolor, which explains their transcriptional induction by GlcNAc. Most likely as the result of the intracellular accumulation of GlcN-6P, nagB deletion mutants fail to grow in the presence of GlcNAc. This toxicity can be alleviated by the additional deletion of nagA. We recently showed that in S. coelicolor, GlcNAc is internalized as GlcNAc-6P via the phosphoenolpyruvate-dependent sugar phosphotransferase system (PTS). Considering the relevance of GlcNAc for the control of antibiotic production, improved insight into GlcNAc metabolism in Streptomyces may provide new leads toward biotechnological applications.